Proceedings of the 2012 International Conference on Communication, Electronics and Automation Engineering - Yang, George (Advances in Intelligent Systems and Computing, 2013)
This book is a collection of selected papers from the 2012 International Conference on Communications, Electronics and Automation Engineering hold in Xi'an, China, August 23-25, 2012. It presents some of the latest research findings in a broad range of interdisciplinary fields related to communications, electronics and automation engineering. Specific emphasis is placed on the following topics: automation control, data mining and statistics, simulation and mathematical modeling, human factors and cognitive engineering, web technology, optimization and algorithm, and network communications. The prime objective of the book is to familiarize the readers with cutting edge developments in the research of electronics and automation engineering with a variety of applications. Hopefully, the book can help researchers to identify research trends in many areas, to learn the new methods and tools, and to spark innovative ideas. .